Atypical Fast-Slow Atrioventricular Nodal Reentrant Tachycardia Incorporating a "Superior" Slow Pathway: A Distinct Supraventricular Tachyarrhythmia. Issue 2 (12th January 2016) - Kaneko, Yoshiaki; Naito, Shigeto; Okishige, Kaoru; Morishima, Itsuro; Tobiume, Takeshi; Nakajima, Tadashi; Irie, Tadanobu; Ota, Masaki; Iijima, Takafumi; Iizuka, Takashi; Tamura, Mio; Tamura, Shuntaro; et al.
Abstract : Background—: The existence of an atypical fast-slow (F/S) atrioventricular nodal reentrant tachycardia (AVNRT) including a superior (sup) pathway with slow conductive properties and an atrial exit near the His bundle has not been confirmed. Methods and Results—: We studied 6 women and 2 men (age, 74±7 years) with sup-F/S-AVNRT who underwent successful radiofrequency ablation near the His bundle. Programmed ventricular stimulation induced retrograde conduction over a superior SP with an earliest atrial activation near the His bundle, a mean shortest spike-atrial interval of 378±119 milliseconds, and decremental properties in all patients. sup-F/S-AVNRT was characterized by a long-RP interval; a retrograde atrial activation sequence during tachycardia identical to that over a sup-SP during ventricular pacing; ventriculoatrial dissociation during ventricular overdrive pacing of the tachycardia in 5 patients or atrioventricular block occurring during tachycardia in 3 patients, excluding atrioventricular reentrant tachycardia; termination of the tachycardia by ATP; and a V-A-V activation sequence immediately after ventricular induction or entrainment of the tachycardia, including dual atrial responses in 2 patients. Elimination or modification of retrograde conduction over the sup-SP by ablation near the right perinodal region or from the noncoronary cusp of Valsalva eliminated and confirmed the diagnosis of AVNRT in 4 patients each. Conclusions—: sup-F/S-AVNRT is a distinct supraventricular tachycardia, incorporating an SP located above the Koch triangle as the retrograde limb, that can be eliminated by radiofrequency ablation.